PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL TEAM GAMES TOURNAMENT (TGT) DI KELAS IV SDN 33 PASAMAN - Yuri Mainasni; Masniladevi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the low learning outcomes of students because teachers have not used innovative learning models and the learning process is still teacher-centered, so that students are still less active in the learning process. The aim of this research is to describe the improvement in student learning outcomes in Pancasila education learning using the model Team Games Tournament (TGT) in class IV at SDN 33 Pasaman. This research is classroom action research (PTK) which uses qualitative and quantitative approaches. Two cycles were carried out, namely cycle I consisting of 2 meetings and cycle II consisting of 1 meeting. Each cycle includes four stages, namely planning, implementation, observation and reflection. The subjects of this research were teachers and 18 class IV students at SDN 33 Pasaman. This research data was obtained from the assessment of teaching modules, implementation processes, and learning outcomes. Data collection techniques use test and non-test sheets. The results showed an increase from cycle I to cycle II. The increase in research results was in: a) the first cycle teaching module, namely 91.06% (very good) and increased in the second cycle to 96.42% (very good), b) Implementation in the first cycle teacher aspect, namely 83.33% ( good) and increased in cycle II to 95.83% (very good), in the student aspect of cycle I, namely 83.33% (good) and increased in cycle II to 95.83% (very good), c) Learning outcomes cycle I students was 79.02% (fair) and increased in cycle II to 93.40% (very good). Based on these results, it can be concluded that using the Team Games Tournament (TGT) model can improve student learning outcomes in Pancasila education learning.